Advances in Grape Seed Oil Extraction Techniques and Their Applications in Food Products: A Comprehensive Review and Bibliometric Analysis - Jaime Laqui-Estaña; Elías Obreque-Slier; Nidia García-Nauto; Erick Saldaña (Foods)
Global wine production has grown, resulting in an increase in waste within the industry. This has raised concerns among producers and scientists worldwide, prompting them to seek solutions for its management. The aim is to explore the latest advancements in using grape seed oil as a byproduct and its applications within the food industry. To achieve this, a bibliometric analysis was conducted using the Scopus database covering the period from 1990 to 2023. Additionally, a comprehensive literature review was conducted on extraction techniques, compositions, properties, and innovative applications in food. A bibliometric analysis revealed that interest in grape seed oil has grown over the past fifteen years. The majority of research on this grape byproduct is concentrated in Asian countries. Grape seed oil is a rich source of lipophilic compounds, including fatty acids, phytosterols, and vitamin E, which provide antioxidant and antimicrobial properties. The literature indicates that only oil obtained through pressing is used in food products, such as meat products, dairy drinks, and chocolates, either directly or in emulsions. These findings suggest that further research and innovation are needed to explore how this waste can be used in new food sources, particularly in countries with high wine production.